Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s11432-014-5269-3
|View full text |Cite
|
Sign up to set email alerts
|

Extreme learning machines: new trends and applications

Abstract: Extreme learning machine (ELM), as a new learning framework, draws increasing attractions in the areas of large-scale computing, high-speed signal processing, artificial intelligence, and so on. ELM aims to break the barriers between the conventional artificial learning techniques and biological learning mechanism and represents a suite of machine learning techniques in which hidden neurons need not to be tuned. ELM theories and algorithms argue that "random hidden neurons" capture the essence of some brain le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(50 citation statements)
references
References 56 publications
1
48
0
1
Order By: Relevance
“…The ELM algorithm has gradually been employed to determine soil properties such as soil heavy metals, soil temperature, and soil moisture, due to its excellent generalization performance and global optimal property [34][35][36]. Most prominently, ELM has a faster learning speed than classical artificial neural networks (ANN) because it simplifies the training processes by randomly selecting the parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The ELM algorithm has gradually been employed to determine soil properties such as soil heavy metals, soil temperature, and soil moisture, due to its excellent generalization performance and global optimal property [34][35][36]. Most prominently, ELM has a faster learning speed than classical artificial neural networks (ANN) because it simplifies the training processes by randomly selecting the parameters.…”
Section: Introductionmentioning
confidence: 99%
“…We use Matlab software running on Windows 8 machine with Intel Core i7 processor. The weights were generated randomly between [-0.4, 0.6] using equations (1)(2)(3)(4) The experiments were run 10 times for each value of error threshold and the average value is taken. The best results is shown in Table 1.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…Extreme learning machine (ELM) [1] is one of the leading trends for fast learning. Unlike the other traditional learning algorithms, for example, Back Propagation-based neural networks, or support vector machine (SVM)], the parameters of hidden layers of ELM are randomly established and need not be tuned, thus the training of hidden nodes can be established before the inputs are acquired.…”
Section: Introductionmentioning
confidence: 99%
“…Then, from the second trial, we update the reference point x * d and feedforward force f d in the reference model iteratively (39) and (40). We set 20 trials for exploration, and the estimations of K 0 and x b of the spring are shown in Fig.…”
Section: A Interaction With a Springmentioning
confidence: 99%
“…Extreme learning machine (ELM) is a unified framework of the generalized single-hidden layer feedforward networks (SLFN) [38] [39]. It is distinctive that the weights of input samples and the bias of activation functions can be randomly chosen in the training process of the ELM.…”
Section: Introductionmentioning
confidence: 99%